Estimating trunk fat in children according to sex using basic somatic readings: an opportunity for improving evaluation among girls - Manuel Moya; Virginia Pérez-Fernandez (BMC, 2021)
Abstract Background The fat mass estimators waist-to-height ratio (WHtR) and relative fat mass-pediatric (RFMp) complement the widely accepted body mass index (BMI) in obesity evaluation. Aims of the Study: Conduct an easy appraisal of trunk fat and the cardiometabolic risk associated with pediatric obesity. Methods A total of 472 children (39% boys in the total sample) were classified as underweight, normal weight, overweight or obese (nutritional groups, NGs) according to BMI Z-score after initial anthropometric data were obtained and ad hoc exclusion criteria were applied. WHtR and RFMp (% of total fat) were calculated for each group, associations were assessed through multiple linear regression (MLR), and differences between sexes were evaluated (medians, IQR). Results The mean age (mean (95% CI)) was 10.8 y (10.1-11.1). The values in the total sample were as follows: WHtR, 0.5 (0.49-0.51) and RFMp%, 32.3 (31.7-33.0). In the overweight group, the values were as follows: WHtR, 0.51 (0.50-0.52) and RFMp(%), 34.2 (33.3-35.1). In the obese group, the values were as follows: WHtR, 0.56 (0.55-0.57) and RFMp(%), 37.8 (36.9-38.6). The associations were as follows (NG; independent variables): In the NG, adjusted R2 values were between 0.74 and 0.78. In the total sample, the beta coefficient was 3.36 (P < 0.001) for RFMp for girls; for waist circumference (WC), the beta coefficient was 2.97 (P < 0.001), and for WHtR the beta coefficients were − 0.01 (p < 0.001) and 0.03 (p < 0.001),for girls and for WC respectively. The sex differences were as follows: BMI exhibited no differences in the NG (Mann-Whitney U). WHtR (median (IQR)) differed (M vs. F) in the total sample (0.49 (0.45-0.54) vs. 0.52 (0.45-0.56), p < 0.004); in the overweight group (0.51 (0.48-0.53) vs. 0.54 (0.51-0.55), p < 0.001); and in the obese group (0.55 (0.52-0.57) vs. 0.57 (0.54-0.60), p < 0.004). RFMp (%) differed in the total group (29.21 (24.27-32.92) vs. 36.63 (30.2-39.51), p < 0.001); in the overweight group (31.24 (28.35-32.35) vs. 37.95 (35.75-38.82), p < 0.001) and in the obese group (35.89 (32.05-36.15) vs. 40.63 (38.27-42.42), p < 0.001). Conclusions WHtR and RFMp are simple and reliable indices that do not require centile charts. Their values, including waist circumference, can be used to estimate the different trunk fat components in boys and girls better than BMI, especially if individuals are overweight or obese. RFMp proved to be more reliable as it considers sex. Both should be included in routine anthropometric readings.